The Reception of Health Information To Reduction Stunting - Puspasari, Cindenia; Mardhiah, Ainol; Husniati, Ade Muana (Universitas Mercu Buana, 2025)
The main causes of stunting can be caused by a lack of nutrition and nutritional intake as a child's needs, off-base child rearing designs due to need of information and instruction for pregnant ladies and breastfeeding moms, lacking sanitation within the living environment such as need of clean water offices and inaccessibility of can offices and constrained get to. wellbeing offices required for pregnant ladies, breastfeeding mothers and toddlers. Malnutrition is a global issue. It is therefore important to have a health communication strategy when providing health information to the community. Using receptivity theory to communicate health information can be a long-term strategy to reduce the prevalence of stunting. There are several receptive analysis strategies that can be implemented to reduce the prevalence of stunting, including individual acceptability in processing information, provision of appropriate information in terms of language, acceptability in understanding media preferences, development of environmental perception factors, dissemination of credible information in influencing the community, and evaluation of information in stunting information dissemination strategies.